2018
DOI: 10.1002/pssa.201800617
|View full text |Cite
|
Sign up to set email alerts
|

Interface Properties of GaP/Si Heterojunction Fabricated by PE‐ALD

Abstract: The properties of n‐GaP/p‐Si interface as well as their influence on solar cell performance are studied for GaP layers grown by low‐temperature (380 °C) plasma‐enhanced atomic layer deposition (PE‐ALD). The influence of different plasma treatments and RF power values are explored. The increase of RF power leads to a growth transition from amorphous (a‐GaP) to microcrystalline GaP (μc‐GaP) with either amorphous‐GaP/Si or epitaxial‐GaP/Si interface, respectively. However, when continuous hydrogen plasma is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 33 publications
0
16
0
8
Order By: Relevance
“…A negative effect of the high RF power hydrogen plasma used in this process was reported in Gudovskikh et al and Geissbuhler et al, where the damage in the Si subsurface region was observed by TEM. Moreover, a defect‐rich area was detected in Si within 30–50 nm of the GaP/Si interface by admittance spectroscopy . On the contrary, the low lateral conductivity of the GaP/Si heterojunction fabricated with hydrogen plasma did not allow us to perform Hall effect measurements in the previous study.…”
Section: Electrical Properties Of the Gap/si Interfacementioning
confidence: 78%
See 3 more Smart Citations
“…A negative effect of the high RF power hydrogen plasma used in this process was reported in Gudovskikh et al and Geissbuhler et al, where the damage in the Si subsurface region was observed by TEM. Moreover, a defect‐rich area was detected in Si within 30–50 nm of the GaP/Si interface by admittance spectroscopy . On the contrary, the low lateral conductivity of the GaP/Si heterojunction fabricated with hydrogen plasma did not allow us to perform Hall effect measurements in the previous study.…”
Section: Electrical Properties Of the Gap/si Interfacementioning
confidence: 78%
“…Damaged regions in Si near the interface could be observed in the samples prepared under continuous hydrogen plasma. However, the most important is the fact that the first 3–5 nm of GaP was grown epitaxially on the Si surface for both processes as was previously reported …”
Section: Growth Details and Structural Propertiesmentioning
confidence: 97%
See 2 more Smart Citations
“…The integration of silicon with III‐V semiconductors via ALD‐grown nucleation layers is investigated in ref. , while ref. is about quantum cutting, and ref.…”
mentioning
confidence: 99%